Comparison of the Diagnostic Performance of Five Clinical Questionnaires for Chronic Obstructive Pulmonary Disease - Alirio R. Bastidas; Eduardo Tuta-Quintero; José S. Arias; Diana Cufiño; Diana Moya; Daniel Martin; Faure Rodríguez; Carolina Aponte-Murcia; Doris M. Pumarejo; Maria A. Bejarano; Geraldine Ospina; Lina M. Morales; et al. (Canadian Respiratory Journal)
Background. Chronic obstructive pulmonary disease (COPD) remains one of the most prevalent pathologies in the world and is among the leading causes of mortality and morbidity, partially due to underdiagnosis. The use of clinical questionnaires to identify high-risk individuals to take them to further diagnostic procedures has emerged as a strategy to address this problem. Objective. To compare the performance of the COULD IT BE COPD, CDQ, COPD-PS, LFQ, and PUMA questionnaires for COPD diagnosis. Methods. A cross-sectional study was carried out on subjects who underwent spirometry in the third-level center. Data were collected between January 2015 and March 2020. Bivariate analysis was performed between the study variables and the presence of COPD. The area under the receiver operating characteristics curve (AUC-ROC), sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), positive likelihood ratio (LR+), and negative likelihood ratio (LR−) for each questionnaire were calculated. The AUC-ROCs were compared with the DeLong test, considering a p value <0.05 statistically significant. Results. 681 subjects met the inclusion criteria and were taken to the final analysis. The prevalence of COPD was 27.5% (187/681). The mean age of the subjects was 65.9 years (SD ± 11.79); 46.3% (315/681) were female, and 83.6% (569/681) reported respiratory symptoms. Statistically significant relationship was found for COPD diagnosis with male sex, older age, respiratory symptoms, and exposure to wood smoke (p value <0.05). The AUC-ROCs of the questionnaires were between 0.581 and 0.681. The COULD IT BE COPD questionnaire had a lower discriminatory capacity AUC-ROC of 0.581, concerning the other scores (DeLong test, p = 0.0002). Conclusion. The CDQ, COPD-PS, LFQ, PUMA, and COULD IT BE COPD questionnaires have acceptable performance for the diagnosis of COPD together with low sensitivity and specificity. Therefore, its use must be complemented with other diagnostic tests or techniques such as pulmonary function tests.